Distribution and enrichment of trace metals in surface marine sediments collected by the manned submersible Jiaolong in the Yap Trench, northwest Pacific Ocean. (October 2018) - Yang, Jichao; Cui, Zhen; Dada, Olusegun A.; Yang, Yaomin; Yu, Hongjun; Xu, Yue; Lin, Zhen; Chen, Yu; Tang, Xin
Abstract: In this study, we carried out grain size and heavy metal analyses and also assessed heavy metal enrichment and ecological risk indices in ten sediment samples collected by the manned submersible Jiaolong at different segments of the Yap Trench. The results showed that the sediments in the Yap Trench were mainly slumping deposits composed of sandy silt. Heavy metals in the sediments showed different spatial distribution patterns from north to south direction of the trench. The distribution pattern of these heavy metals also differed in the eastern and western flanks of the trench. From the results of the enrichment factors, only arsenic, chromium, and manganese showed a slight enrichment. However, all elements were affected by natural factors. Further, most elements showed a low ecological risk, and only arsenic showed a moderate risk at two stations. Finally, the potential ecological risk of the whole study area was at a low level. Highlights: The sediments in the Yap Trench are mainly slumping deposits composing of sandy silt. The concentration of heavy matals has increased in the past 30, 000 years, but still maintain natural source characteristics. The potential ecological risk index results also indicate a low ecological risk of the heavy metals. The arsenic elelment in some stations shows moderate ecological risk.